PENGARUH REMITANSI, FOREIGN DIRECT INVESTMENT, DAN INFLASI TERHADAP PERTUMBUHAN EKONOMI INDONESIA - Kirana, Devi Natalia; Ayuningsasi, Anak Agung Ketut (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2022)
Economic growth is an indicator to find out how successful a country's economic development is and indicates that the results of development have been evenly distributed. This study aims to analyze the simultaneous effect of remittances, foreign direct investment (FDI), and inflation on Indonesia's economic growth and to analyze the effect of remittances, foreign direct investment (FDI), and inflation partially on Indonesia's economic growth. The location of this research was conducted in Indonesia with a total of 30 observations, namely time series data from the period 1990 to 2019. The analysis technique used was multiple linear regression analysis with the software used was SPSS. Based on the results of the analysis using the F-test, it was found that remittances, FDI, and inflation simultaneously had a significant effect on Indonesia's economic growth. Based on the results of the analysis using the t-test (partial) it was found that remittance has a positive and significant effect on Indonesia's economic growth, foreign direct investment (FDI) has a positive and significant effect on Indonesia's economic growth and inflation has a negative and insignificant effect on Indonesia's economic growth